2020
DOI: 10.1093/biolre/ioaa096
|View full text |Cite
|
Sign up to set email alerts
|

Engineering monoclonal antibody-based contraception and multipurpose prevention technologies†

Abstract: Abstract Sexually transmitted infections are highly prevalent, and over 40% of pregnancies are unplanned. We are producing new antibody-based multipurpose prevention technology products to address these problems and fill an unmet need in female reproductive health. We used a Nicotiana platform to manufacture monoclonal antibodies against two prevalent sexually transmitted pathogens, HIV-1 and HSV-2, and incorporated them into a vaginal film (MB66) for preclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Further research is required to determine if more than 1 anti-HIV antibody is needed for optimal efficacy and to avoid HIV escape mutations. Thus, additional mAbs against HIV-1 and other STI pathogens, as well as contraceptive mAbs [ 53 ], could be included in an eventual commercial mAb-MPT product to provide more comprehensive protection.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to determine if more than 1 anti-HIV antibody is needed for optimal efficacy and to avoid HIV escape mutations. Thus, additional mAbs against HIV-1 and other STI pathogens, as well as contraceptive mAbs [ 53 ], could be included in an eventual commercial mAb-MPT product to provide more comprehensive protection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this phase 1 clinical study, there is variability in film dissolution rate, which will influence changes in release kinetics, and PK testing was not conducted between days 1 through 7 [ 45 ]; therefore, further testing is required for this formulation. Nevertheless, due to the promising inhibitory effects of MB66, Anderson et al suggested utilizing “human contraceptive antibody” (HCA) for an MPT vaginal film for HIV, HSV, and contraception [ 103 ]. HCA is the only antisperm antibody in advanced development and shown to promote sperm agglutination, trap flagellating sperm in human midcycle cervical mucus (mucus trapping), and promote viral neutralization of HIV and HSV [ 103 ].…”
Section: Vaginally Delivered Mptsmentioning
confidence: 99%
“…In addition to manufacturing scale requirements, cost is a clear constraint for such a product. We estimate that COGs for a dose would need to be no more than $0.25, 44 translating to $6.25 per gram, a goal not yet achieved by existing manufacturing platforms.…”
Section: Hiv Prevention (Mucosal Delivery)mentioning
confidence: 98%
“…Prevention of vaginal transmission of HIV and HSV coupled with a contraceptive antibody has been discussed above. 42,44 There are more than 10 mAbs in preclinical or early stage clinical development for enteric diseases 2 that may be amenable to oral delivery. In the respiratory tract, the limited bioavailability of systemically delivered IgG in tissues affected by the disease, especially the lungs, may be limiting the efficacy of mAbs for diseases such as RSV, influenza and SARS-CoV-2.…”
Section: Metric Ton Manufacturing: Challenges and Opportunitiesmentioning
confidence: 99%